2016
DOI: 10.1128/aac.00209-16
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Factors Associated with Antibiotic Prescribing for Respiratory Tract Infections

Abstract: Antibiotic use is a modifiable driver of antibiotic resistance. In many circumstances, antibiotic use is overly broad or unnecessary. We systematically assessed factors associated with antibiotic prescribing for respiratory tract infections (RTI). Studies were included if they used actual (not self-reported or intended) prescribing data, assessed factors associated with antibiotic prescribing for RTIs, and performed multivariable analysis of associations. We searched Medline, Embase, and International Pharmace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
153
1
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(181 citation statements)
references
References 67 publications
(122 reference statements)
12
153
1
8
Order By: Relevance
“…Our research is focused on patient expectation for receiving antibiotics for RTIs, of which most are viral infections not requiring antibiotics. Inappropriate antibiotic prescribing for RTIs can lead to over‐prescribing and contribute to antimicrobial resistance . To understand this behaviour, it is essential to identify the contributing components in the prescribing process.…”
Section: Discussionmentioning
confidence: 99%
“…Our research is focused on patient expectation for receiving antibiotics for RTIs, of which most are viral infections not requiring antibiotics. Inappropriate antibiotic prescribing for RTIs can lead to over‐prescribing and contribute to antimicrobial resistance . To understand this behaviour, it is essential to identify the contributing components in the prescribing process.…”
Section: Discussionmentioning
confidence: 99%
“…Despite URTIs generally being minor illnesses, they result in an appreciable number of medical consultations globally 87,[199][200][201][202][203] . The number of healthcare consultations combined with parental and patient pressure increases antibiotic use for URTIs including LMICs thereby increasing AMR rates 88,153,200,[204][205][206][207][208][209] . Patients or parents who are concerned about their or their child's respiratory illness are likely to seek treatment, and want an antibiotic, especially if they perceive the illness as severe 21,209,210 .…”
Section: Aetiology Of Urtis and Symptomsmentioning
confidence: 99%
“…Education initiatives for doctors starting at medical school may be necessary in LMICs where there are concerns with current training and its impact on reducing inappropriate prescribing of antibiotics 48,50,315,[319][320][321][322][323][324][325][326][327] . Improving communication between family doctors and patients should help address concerns that physicians want to help their patients, and tend to overestimate patients' expectations regarding their wish to be prescribed an antibiotic for their URTI 21,153,156 . Physicians are also more likely to prescribe an antibiotic if they feel under pressure 108,328,329 .…”
Section: Physiciansmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review on antibiotic prescribing for respiratory tract infections, found that acute bronchitis and features on physical exam were factors associated with antibiotic prescribing [10]. Physician’s perception of patient desire for antibiotics was a stronger prediction for prescription than patient desire for an antibiotic.…”
Section: Introductionmentioning
confidence: 99%